The mechanisms of acquired resistance to anti-EGFR drugs in non-small cell lung cancer not associated with T790m mutation and their significance in clinical practice - E. V. Karabina; L. N. Lubchenko; M. M. Davydov (Успехи молекулярной онкологии)
The prospects of treatment strategies for patients with non-small cell lung cancer (NSCLC) featuring the acquired resistance to tyrosine kinase inhibitors, not associated with the Т790М mutation, are quite vast from a scientific point of view, but in routine clinical practice they are not yet available in full. Understanding the mechanisms of acquired resistance to tyrosine kinase inhibitors is important for clinicians from the perspective of the possibility of forming more effective options for the second and subsequent treatment of NSCLC. The most studied and frequent mechanism causing the formation of the acquired resistance is the appearance of the Т790М mutation in 20 exons of the EGFR gene. This article describes the current understanding of the mechanisms of acquired resistance to tyrosine kinase inhibitors not associated with the mutation of T790M, the evolution of views concerning the treatment of NSCLC, progressing in the course of the treatment by this group of drugs. Taking into account the diversity of unresolved issues and directions of further scientific research, we should not forget about the available research results and the ability to use the described options in routine clinical practice in a proper way.